Analytical modelling of edge chipping in scratch of soda-lime glass considering strain-rate hardening effect. Issue 18 (15th September 2021) - Shi, Haoyu; Liu, Gongyu; Yang, Guilin; Bi, Qingzhen; Zhao, Yongjie; Wang, Bo; Sun, Xu; Liu, Xiaoling; Qi, Huan; Xu, Wenhao; Thein, ChungKet; Li, Hao Nan
Abstract: Soda-Lime Glass (SLG) has been widely used in the creation of highly-functionalised optical devices. However, machining of SLG easily resulted in various defects. Among these defects, edge chipping (EC) can be treated as the most damageable in terms of both mechanical properties and optical performances. Although efforts have been paid to this topic, previous investigations (i) focused on edge chipping in low strain rate, which was 10 1 -10 2 times lower than the ones in real machining, (ii) assumed edge chipping shape as circular, while the experiments in this work proved this assumption might be inaccurate in high strain rate circumstances, and (iii) were experimental efforts, resulting in limited knowledge of process principles. To fill this gap, this paper aims to propose an analytical model to calculate the size and the shape of edge chipping in scratch of soda-lime glass with the special consideration of strain-rate hardening effect. A series of experimental trials were performed to validate the model accuracy under different parameters. The details in scratching process were discussed by force analysis. A typical model application was given as well, which was designing the machining strategy based on the proposed model so that a required region with limited edge chipping can be obtained. Considering the research gaps mentioned above, the key findings in this paper are expected to be meaningful and helpful to provide references in the real fabrication of high-valued optical devices made of SLG.